Cultura Audiovisual e Formação de Educadores: Possibilidades e Limites em Práticas Educomunicativas - Cabello, Camila Faustinoni (2011)
Audiovisual culture and teacher development: possibilities and limits in educommunicative practices aimed at investigating the possibilities and limits in the uses of educomunicative practices to transpose barriers and to approximate educators and students, based on teachers development to the production of audiovisual culture in school environments. The research was based on Paulo Freire and Henry Giroux for the concepts of education and teachers development; Fernando Hernandez and Marshall McLuhan for the audiovisual culture and means of communication; Mario Kaplún and Ismar de Oliveira Soares for the concept of educommunication. The present study is a qualitative action-research, based on formative experiences offered to educators for the production of audiovisual culture by means of educommunicative practices, in the form of video, radio and comics. The research data were collected and registered in audio in cultural circles, according to Paulo Freire proposals, where the research participants discussed the impressions about the experiences. The possibilities and limitations were observed from the subjective, collective and structural axles in order to examine and analyze the major dimensions of the educational work. The results allowed to observe that the teacher training alone does not include transformation of the relationships in the school context but theoretically grounded institutional political-pedagogical projects aligned with the educommunicative proposal may be provocative of changes in a broader and more effective scope.